ILLUSTRATION OF THE APPLICATION OF SHALLOT RUBBINGON DECREASING BODY TEMPERATURE IN CHILDREN AGED 2-5 YEARS WITH FEVER IN DESA KEMOJING, KEMANGKON DISTRICT PURBALINGGA REGENCY - Setiani, Purwaningsih Endah; Astuti, Dwi; Sulistyowati, Priyatin (PT. Jurnal Center Indonesia Publisher, 2025)
Febris fever is a condition in which body temperature rises above normal due to an increase in the temperature-regulating center located in the hypothalamus. Red Onion can be used for compress because they contain the organic sulfur compound Allylcysteine Sulfoxide. After applying an onion compress, body temperature decreases because blood flow returns to the blood vessels near the skin's surface, thus optimizing heat dissipation.To determine the effectiveness of applying onion compress to children with fever. This study used a descriptive case study approach and was conducted in Kemojing Village. After applying onion compresses for three days, with each session lasting 15 minutes, the children's body temperature decreased. The initial body temperature was 38.4°C, which decreased to 36.8°C by the end of the third day. Using onion compresses on children with fever can effectively reduce their body temperature.